FEMALE REPRODUCTION IN THE LIZARD Ameiva ameiva (SQUAMATA: TEIIDAE) IN A CAATINGA SITE OF NORTHEASTERN BRAZIL - Sales, Raul Fernandes Dantas (2020)
Ameiva ameiva is a lizard species widely distributed in Central and South America. In this study, we present data on clutch size and duration of reproductive cycle in a population of A. ameiva from a Caatinga site in northeastern Brazil, looking to answer the following questions: 1) What is the average clutch size in this population? 2) Is clutch size associated with body size of females? 3) Is reproduction continuous or seasonal? The fieldwork to collect the lizards consisted of monthly trips from October 2008 to September 2010. Additionally, from June 2009 to May 2010, we registered the abundance of hatchlings and adults in the population by counting active lizards in the field. We collected 15 adult females, ten of which were in reproductive condition. Average clutch size was 5.3 ± 0.7 (range: 2–8, N = 10), and was significantly associated with body size of females. Reproductive females were registered both in the rainy and dry seasons, suggesting a prolonged reproductive period throughout the year. However, the decline in adult abundance during the peak of dry season and the absence of hatchlings in the population during four consecutive months are indications that females did not reproduce continuously during 2009-2010.Keywords: Clutch size; Life story; Reproductive cycle; Seasonality